2003
DOI: 10.1590/s0101-20612003000200025
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento higroscópico da farinha de pupunha (Bactris gasipaes)

Abstract: Ciênc. Tecnol. Aliment., Campinas, 23(2): 251-255, maio-ago. 2003 251Comportamento higroscópico da farinha de pupunha (Bactris gasipaes), Ferreira e Pena -INTRODUÇÃOA pupunheira (Bactris gasipaes) é uma palmeira nativa dos trópicos úmidos americanos, e segundo CLEMENT [5] é a única espécie da família Palmae. Produz frutos comestíveis de sabor muito apreciado, definitivamente integrados aos hábitos alimentares da Região Amazônica [17]. A polpa dos frutos, cuja composição média é apresentada na Tabela 1, é geral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0
21

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 7 publications
4
27
0
21
Order By: Relevance
“…The same behaviors were observed by Telis et al (2000) for persimmon bark and pulp, Yoshida (1996) for adsorption isotherms of moisture of lyophilized super sweet is constant and independent of temperature (GABAS et al, 2007). However, other authors found that X m depends on the temperature (YOSHIDA, 1996;MISHRA;ORAIKUL;TEMELLI, 1996;ALEXANDRE, 2005;FERREIRA;PENA, 2003).…”
Section: Adsorption Isothermssupporting
confidence: 54%
“…The same behaviors were observed by Telis et al (2000) for persimmon bark and pulp, Yoshida (1996) for adsorption isotherms of moisture of lyophilized super sweet is constant and independent of temperature (GABAS et al, 2007). However, other authors found that X m depends on the temperature (YOSHIDA, 1996;MISHRA;ORAIKUL;TEMELLI, 1996;ALEXANDRE, 2005;FERREIRA;PENA, 2003).…”
Section: Adsorption Isothermssupporting
confidence: 54%
“…This difference in particle size caused different capacities of absorption and agglomeration of the powders, producing different results in the degree of caking. Costa et al (2003) claim that different variations in the hygroscopic behavior of food powders are attributed to their size, because finer particles have larger contact surface and, therefore, higher number of active sites.…”
Section: Resultsmentioning
confidence: 99%
“…Resultados semelhantes são obtidos por Silva et al( 2010), para isotermas de adsorção do coentro desidratado e, também, por Alcântara et al(2008), para isotermas de adsorção do pedúnculo seco de caju. De acordo com Ferreira & Pena (2003), esse comportamento pode ser provavelmente explicado através de dois mecanismos: 1) o aumento da temperatura pode provocar modificações na estrutura física do produto, disponibilizando um número maior de sítios ativos com afinidade por moléculas de água; ou 2) pode provocar um aumento na solubilidade de solutos intrínsecos ao produto, fazendo com que um número maior de moléculas de água fique retido na monocamada.…”
Section: Resultados E Discussõesunclassified